The Physiological Dormancy and Germination Responses of Brunonia australis and Rhodanthe floribunda to Gibberellic Acid Treatment - Ha, Tuan Minh (Department of Agronomy and Horticulture, IPB University, 2014)
Brunonia australis (Goodeniaceae) and Rhodanthefloribunda (Asteraceae) are two potential Australiannative ower species desired by oricultural markets.However, the species are difcult to propagate. Thisstudy examined internal factors that constraint seedgermination, seed viability and physiological dormancy.The study was conducted during April to May 2009 at theGatton nursery, The University of Queensland GattonCampus to identify the underlying reasons for poorgermination and to provide recommendations forimproving propagation effectiveness. Seeds of B.australis collected in 2003 germinated readilyirrespective of germination media, whereas seedscollected in 2007 and 2008 with high proportion of viableseeds could only germinate with the presence of GA3(100 mg.L ) in germination media though with relatively -1low rates (8.75% and 10.00% respectively) of seedgermination. Seeds of R. floribunda collected in 2003showed a signicant improvement in germination inagar media supplemented with 100 mg.L GA (67.5%) -13 compared to control treatment (10.0%). The resultssuggest that physiological dormancy occurs in bothspecies. The use of GA is recommended for improving 3germination rates of the two species. Further studies onthe effects of different GA concentrations to improve 3seed germination should be conducted.Keywords: Dormancy, germination, gibberellic acid, TZ,viability.